Penguatan Kapasitas Kelompok Tani Hortikultura dalam Pengembangan Bisnis Pembibitan di Desa Pendua Kabupaten Lombok Utara - Muktasam Muktasam; Arifuddin Sahidu; Hayati Hayati (Universitas Mataram, 2022)
Horticulture is an importance farming system in North Lombok due to two reasons, first it provides job to the community, and second it becomes a source of households’ income which is different from food crops. A collaborative project between Mataram University and Massey University – New Zealand called as IFSCA Project (2017 – 2020) has facilitated the adoption and diffusion of horticultural innovations in North Lombok, however two natural disaster, namely earth quake (in mid 2018) and covid-19 pandemy (early 2020) had disturbed the horticulture farming system. The big earth quake destroyed the irrigation channels and some water springs disappeared while the covid-19 pandemy had led to farmers’ difficulties to sell their horticulture products, and a results farmers’ production and incomes decreased significantly. This public service activity was conducted in September 2021 to help farmers addressing issues associated with these horticulture farming system issues. Based on the evaluation results, it was found that farmers’ knowledge and outlooks had improved due to the activity – strengthening the capacity of farmers and farmer group, especially in the area of farming management, the importance of partnership, doing extra-services to the customers, product quality and guarantee, the existence of horticulture clinic), and critical support from the agency such as North Lombok Horticulture Development Agency. This institution has played critical roles in horticulture agribisnis system development, ranging from the input system to the marketing systems of the products, for both seedling and horticulture products. This article presents a summary of the public service activities and results conducted in North Lombok at Pendua Village – Kayangan Subdistrict – North Lombok.